Barriers to Colorectal Cancer Screening in Primary Care Settings: Attitudes and Knowledge of Nurses and Physicians - Muliira, Joshua Kanaabi (Asia Pac J Oncol Nurs, 2016)
OBJECTIVE: Healthcare providers (HCPs) play a critical role in reducing colorectal cancer (CRC) related morbidity and mortality. This study aimed at exploring the attitudes and knowledge of nurses and physicians working in primary care settings regarding CRC screening. METHODS: A total of 142 HCPs (57.7% nurses and 42.3% physicians) participated in a cross-sectional survey. Data were collected using a Self-administered Questionnaire. The participants were clinically experienced (mean = 9.39 years; standard deviation [SD] = 6.13), regularly taking care of adults eligible for CRC screening (62%) and had positive attitudes toward CRC screening (83.1%). Most participants (57%) had low levels of knowledge about CRC screening (mean = 3.23; SD = 1.50). The participants were most knowledgeable about the recommended age for initiating screening (62.7%) and the procedures not recommended for screening (90.8%). RESULTS: More than 55% did not know the frequency of performing specific screening procedures, the upper age limit at which screening is not recommended, and the patients at high-risk for CRC. There were no significant differences between nurses’ and physicians’ attitudes and knowledge. The participants’ perceptions about professional training (odds ratio [OR] = 2.17, P = 0.003), colonoscopy (OR = 2.60, P = 0.014), and double-contrast barium enema (OR = 0.53, P = 0.041), were significantly associated with knowledge about CRC screening. CONCLUSIONS: The inadequate knowledge levels among nurses and physicians may be one of the barriers affecting CRC screening. Enhancing HCPs knowledge about CRC screening should be considered a primary intervention in the efforts to promote CRC screening and prevention.